THE INTERCONNECTION OF EDUCATION AND UPBRINGING IN THE PHILOSOPHICAL VIEWS ADVANCED DURING THE MANGHIT PERIOD - Rajabova Rohila Zakirovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the interconnection of education and upbringing in the socio-philosophical views formed during the Manghit period. It highlights the ideas of the era's thinkers and enlighteners concerning human perfection, moral upbringing, and the acquisition of knowledge. It also examines the significance of education and upbringing in the development of society, as well as the questions of their mutual harmony.